Penolakan Hakim Atas Permohonan Cerai Talak Suami yang Istrinya Selingkuh dalam Tinjauan Hukum Islam - Amaliyah Permata Sari; Alfan Syafi'i (El 'Ailaah, 2026)
Divorce (ṭalāq) is a husband’s prerogative right, and in Indonesia, its execution must be carried out through the Religious Court. In this case, the husband filed for divorce due to his wife’s infidelity, which had caused prolonged conflict. However, the judge rejected the husband’s divorce petition. In fact, divorce on the grounds of adultery that prevents the realization of marital objectives is permitted under Article 116 of the Compilation of Islamic Law (KHI). This study aims to examine the judge’s considerations in rejecting the husband’s divorce petition and to analyze these considerations from the perspective of Islamic law. The research method applied is qualitative, combining field research through interviews with the registrar of the Sumber Religious Court and library research, including classical and contemporary fiqh texts, journal articles, and court rulings. Data collection techniques consisted of semi-structured interviews and documentation. The collected data were then reduced, presented, and concluded using descriptive analysis. The findings show that the judge’s reason for rejecting the husband’s divorce petition was that the witnesses presented were classified as de auditu witnesses, namely those who only heard from the petitioner and were not materially valid. From the perspective of Islamic law, de auditu testimony does not comply with the standard of evidence in Islam, namely bayyinah. Testimony (shahādah) must be able to clearly establish the truth in order to avoid doubt. Therefore, the judge’s consideration in rejecting the husband’s divorce petition was in accordance with Islamic law.